Podzemni prostor/kibernetski prostor - Novljan, Tomaž (Urbani izziv, 2000)
A modern city space is a space where in the vertical and horisontal direction dynamic, nonlinear processes exist, similar as in nature. Alongside the common city surface, cities have underground spaces as well that are increasingly affecting the functioning of the former. It is the space of material and cybernetic communication/transport. The psychophysical specifics of using underground places have an important role in their conceptualisation. The most evident facts being their limited volume and often limited connections to the surface and encresed level of potential dangers of all kinds. An efficient mode for aleviating the efficient mode for aleviating the effects of these specific features are artistic interventions, such as: shape, colour, lighting, all applications of the basic principals of the fractal theory.
Keywords: kibernetski prostor; kiberprostor; kvaliteta; podzemni objekti; tipologija; urbana naselja; urbani razvoj; urbanism; urbanizem